THE INFLUENCE OF FINANCIAL PERFORMANCE ON MARKET PERFORMANCE OF INDONESIAN FINANCE INDUSTRY - Soewignyo, Fanny (JBE (Journal of Business and Economics), 2014)
T he purpose of this study is to examine whether profit per employee and revenue per employee as financial performance measures act as prox ies to market performance measured by market capitalization per employee of Indonesian listed finance industry (banks and non-bank financial institutions).  Using purposive sampling in year 2012 , 56 companies were selected.  Multiple and simple regression analyses were conducted to test the hypotheses.  The result of multiple regression suggests that the increase in profit per employee can lead to a better market capitalization per employee.  However, revenue per employee could not provide a significant influence to market capitalization per employee.  Further examination was conducted with simple regression analysis using profit per employee as independent variable and the finding indicates that approximately 62.4% of variance in market capitalization per employee can be explained by profit per employee and the remaining 37.6%  proportion of variance in market capitalization per employee can be explained by other factors. The results provide guidelines to help investors, managers, as well as academicians to comprehend the importance of profit per employee as a driver  to market performance and to sustain it in Indonesian finance industry.